MODEL BÃHLMANN STRAUB DALAM TEORI KREDIBILITAS - , Affiati Oktaviarina, S.Si., Dr. Rer. Nat. Dedi Rosadi, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The theory of credibility theory is a technique to predict the amount of premium rates in the future based on past experience. One approach models in credibility theory is Bühlmann Straub model was first developed by Bühlmann and Straub is an extension of the Bühlmann model. In this thesis, Bühlmann Straub model applied to insurance data earthquake PT Reinsurance International Indinesia June 2005 edition which contains the Risk and Loss Profile in four years, underwriting the 2001, 2002, 2003, 2004. Earthquake insurance data consists of 20 groups at risk. In this numerical application, researchers used a number of policies and claims severity to calculate the value premium Bühlmann Straub model.